Computer‐assisted vocabulary instruction for students with disabilities: Evidence from an effect size analysis of single‐subject experimental design studies - Mize, Min Kyung; Park, Yujeong; Moore, Tara (Journal of computer assisted learning, 2018)
The purpose of this study was to synthesize the effectiveness of computer‐assisted instruction (CAI) studies aiming to increase vocabulary for students with disabilities in an effort to identify what type of CAI is promising for practice. An extensive search process with inclusion and exclusion criteria yielded a total of 13 single‐subject design studies to be included in the present study. Effect sizes were calculated using a percentage of nonoverlapping data (PND). We also analysed instructional features (e.g., visual supports, auditory supports, font/color selection, and corrective and interactive feedback) from the studies that examined effective instructional design features of CAI. Results indicated (a) the highest PND mean was for secondary school‐aged learners with disabilities; (b) both tablet‐assisted instructions and nontablet‐assisted instruction produced high PND (i.e., highly effective); and (c) although the majority of selected studies included visual and auditory supports in CAI for vocabulary, none of the studies provided opportunities for customization (e.g., student selection of colors and fonts). On the basis of the findings, implications for future research and practice are discussed. Lay Description What is already known about this topic: Technology as instructional aids provides students with disabilities with access to general education curriculum. Students with disabilities can benefit from explicit instruction combined with computer‐assisted instruction or intervention. Technology provides avenues for teachers to create learning opportunities and practices. What this paper adds: The use of visual images, animations, and graphics led to positive academic outcomes of students with disabilities. The use of auditory supports was positively associated with the effectiveness of treatments. Providing students with disabilities with a choice can improve their academic outcomes and motivation. Customization makes computer‐assisted instruction or intervention adaptable for different levels of students with disabilities. Implications for practice and/or policy: Technology and evidence‐based practice might reduce the gap in achievement levels between students with and without disabilities. Teachers should embed with explicit instruction that provides necessary support and structure for students with disabilities.